2011
DOI: 10.1021/ja200312y
|View full text |Cite
|
Sign up to set email alerts
|

Antisense and Antigene Inhibition of Gene Expression by Cell-Permeable Oligonucleotide–Oligospermine Conjugates

Abstract: Oligonucleotides and their derivatives are a proven chemical strategy for modulating gene expression. However, their negative charge remains a challenge for delivery and target recognition inside cells. Here we show that oligonucleotide-oligospermine conjugates (Zip nucleic acids or ZNAs) can help overcome these shortcomings by serving as effective antisense and antigene agents. Conjugates containing DNA and locked nucleic acid (LNA) oligonucleotides are active and oligospermine conjugation facilitates carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
(54 reference statements)
1
40
0
Order By: Relevance
“…We have shown that LNA-CTG binding to the CAG repeats is a strong barrier for retrotranscription as previously suggested (18); and the consequent lack of RT-PCR amplification of fragments spanning the CAG repeat permitted tracking of LNA-CTG binding to mutant HTT-e1 and other genes. The characterization of LNA-CTG dosage effects in HD fibroblasts indicated a preferential binding to the expanded allele with a 6-fold selectivity, which agrees with previous studies focusing on the effect of other ASOs on HTT protein expression (16,17,29,30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have shown that LNA-CTG binding to the CAG repeats is a strong barrier for retrotranscription as previously suggested (18); and the consequent lack of RT-PCR amplification of fragments spanning the CAG repeat permitted tracking of LNA-CTG binding to mutant HTT-e1 and other genes. The characterization of LNA-CTG dosage effects in HD fibroblasts indicated a preferential binding to the expanded allele with a 6-fold selectivity, which agrees with previous studies focusing on the effect of other ASOs on HTT protein expression (16,17,29,30).…”
Section: Discussionsupporting
confidence: 89%
“…LNA-CTG binding to HTT mRNA was determined by the lack of PCR amplification within the LNA-bound region due to the strong incompatibility of LNA-CTG:CAG duplexes with retrotranscription and subsequent PCR amplification (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI83185DS1). 30. Densitometric determinations were normalized to the β-actin PCR product and referred to the mock-transfected condition with a value of 1.…”
Section: Resultsmentioning
confidence: 99%
“…Terminally modified polyamineoligonucleotide conjugates ASOs, siRNAs and DNAzymes with polyamines attached at terminal or internal phosphates have been described (Table 1) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Protonated amines of terminally conjugated polyamines are thought to fold back and associate intramolecularly with the local phosphate linkages of the oligonucleotide backbone, to partially neutralize the negative charges [29].…”
mentioning
confidence: 99%
“…These conjugates lack the polyanionic nature and electrostatic repulsion of the negatively charged phosphate backbones, leading to increased binding affinities and improved cellular uptake. ZNA conjugates were found to reduce huntingtin expression in Huntington disease (HD) patient-derived cells [81]. Although ZNA conjugates are primarily used as probes for real-time PCR, they possess some therapeutically interesting properties.…”
Section: Sugar Group Modifications: Improving Affinity and Reducing Tmentioning
confidence: 99%